Postcolonial/Decolonial Critique and the Theory of International Relations - Aziz Elmuradov (Vestnik MGIMO-Universiteta, 2021)
The article is devoted to the discussion of the role of postcolonial/decolonial critique and its contribution to the theory of international relations. Intersecting with multiple disciplines and area studies, the postcolonial/decolonial critique offers a broad view not only on the cultural heritage of colonialism/imperialism as such, but also on the more complex and multifaceted challenges facing international relations – the coloniality of power and geopolitics of knowledge – and conditions of their emergence. Postcolonial/decolonial approaches foster critical engagement with Eurocentric narratives in social sciences, countering teleological or linear representations of modernity. Despite its importance, postcolonial/decolonial thought penetrated the theory of international relations rather late. The two fields of intellectual quest have developed not only separately, but they have often diverged in their very epistemological constitution. Based on a review of an extensive literature, the author explores the links between the production of postcolonial knowledge and the theory of international relations. Thus, the author illuminates the problems of modern political science and international studies, on the one hand, and on the other hand, emphasizes the need to make the theory of IR accessible to a variety of new global perspectives. The formation of integrative approaches in the study of world politics should provide a new consolidation of both political science and international studies and a productive interaction of these areas of knowledge.